Body composition and plasma total‐tau, neurofilament light chain, and amyloid‐β: A population‐based study - Tosca O. E. deCrom; Mohsen Ghanbari; Trudy Voortman; M. Arfan Ikram (Alzheimer’s & Dementia: Diagnosis, Assessment & Disease Monitoring, 2024)
Abstract A higher body mass at older age has been linked to a lower risk of dementia. This unexpected trend may be explained by age‐related lean mass depletion, or methodological issues such as the long preclinical phase of dementia or competing risks. Focusing on preclinical markers of dementia may overcome these issues. Between 2002 and 2005, body composition and plasma total‐tau, neurofilament light chain (NfL), amyloid‐β40, and amyloid‐β42 were measured in 3408 dementia‐free participants from the population‐based Rotterdam Study. The cross‐sectional associations between body composition and plasma markers were determined using linear regression models. Whole body and fat mass, but not lean mass, were positively associated with total‐tau, while all these measures were inversely associated with NfL. Apart from an inverse association between lean mass and amyloid‐β40, body composition measures were not associated with plasma amyloid‐β. Our findings suggest distinct effects of body composition on neurodegeneration.